The Savvy Survey #14: Mixed-Mode Surveys - Glenn D. Israel; Jessica L. Gouldthorpe (EDIS)
As part of the Savvy Survey Series, this publication provides Extension faculty with an overview of the mixed-mode survey. There are many methods that can be combined for conducting mixed-mode surveys, including face-to-face interviews, telephone interviews, web surveys, and mail questionnaires. This publication focuses specifically on one type of mixed-mode survey that uses both e-mail and postal mail for sending survey invitations, as well as a website and paper questionnaires for collecting responses. Mixed-mode surveys such as this are well suited for conducting needs assessments for program development or follow-up surveys for program evaluation. This 11-page fact sheet was written by Jessica L. Gouldthorpe and Glenn D. Israel, and published by the UF Department of Agricultural Education and Communication, April 2014.